Energy Upconversion in GaP/GaNP Core/Shell Nanowires for Enhanced Near‐Infrared Light Harvesting. Issue 21 (9th July 2014) - Dobrovolsky, Alexander; Sukrittanon, Supanee; Kuang, Yanjin; Tu, Charles W.; Chen, Weimin M.; Buyanova, Irina A.
<x xml:space="preserve">Abstract</x> Semiconductor nanowires (NWs) have recently gained increasing interest due to their great potential for photovoltaics. A novel material system based on GaNP NWs is considered to be highly suitable for applications in efficient multi‐junction and intermediate band solar cells. This work shows that though the bandgap energies of GaNxP1‐x alloys lie within the visible spectral range (i.e., within 540–650 nm for the currently achievable x < 3%), coaxial GaNP NWs grown on Si substrates can also harvest infrared light utilizing energy upconversion. This energy upconversion can be monitored via anti‐Stokes near‐band‐edge photoluminescence (PL) from GaNP, visible even from a single NW. The dominant process responsible for this effect is identified as being due to two‐step two‐photon absorption (TS‐TPA) via a deep level lying at about 1.28 eV above the valence band, based on the measured dependences of the anti‐Stokes PL on excitation power and wavelength. The formation of the defect participating in the TS‐TPA process is concluded to be promoted by nitrogen incorporation. The revealed defect‐mediated TS‐TPA process can boost efficiency of harvesting solar energy in GaNP NWs, beneficial for applications of this novel material system in third‐generation photovoltaic devices.